Cardiometabolic risk assessment by anthropometric and biochemical indices in mexican population - Quirino-Vela, Luz; Mayoral-Chavez, Miguel; Pérez-Cervera, Yobana; Ildefonso-García, Osiris; Cruz-Altamirano, Elizabeth; Ruiz-García, Monserrat; Alpuche, Juan (Frontiers in Endocrinology, 2025)
BackgroundCardiometabolic risk (CMR) factors, including obesity, hypertension, hyperglycemia, and dyslipidemia, are major contributors to global morbidity and mortality. Although gold-standard diagnostic methods for obesity and insulin resistance exist, they are costly and inaccessible in resource-limited settings. Conventional anthropometric measures underestimate parameters that enhance risk prediction and fail explaining the complex relationship between adipose tissue distribution and metabolic dysfunction. This study evaluated and compared the diagnostic accuracy of 15 conventional and non-conventional anthropometric and biochemical indices for identifying CMR factors in Mexican adults. We hypothesized that non-conventional indices would demonstrate superior diagnostic performance compared with traditional measures.MethodsWe analyzed data from 1,876 participants aged 20–80 years from the 2022 National Health and Nutrition Survey (ENSANUT). Anthropometric indices, including body mass index (BMI), waist-to-height ratio (WHtR), body roundness index (BRI), deep abdominal adipose tissue index (DAAT), and weight-adjusted waist index (WWI), were calculated alongside biochemical indices such as HOMA-IR, triglyceride-glucose index (TG), and combined indices like TG*BMI and TG*WC. Receiver operating characteristic (ROC) curve analysis evaluates diagnostic performance, with sex-stratified analyses conducted to determine optimal cut-off values.ResultsNon-conventional indices demonstrated superior diagnostic performance across all outcomes. For obesity detection, TG*BMI achieved the highest area under the curve (AUC=0.972), followed by WHtR and BRI (AUC=0.934). For CMR assessment, BRI showed perfect discrimination (AUC=1.000), whereas TG*WC (AUC=0.976) and LAP (AUC=0.963) demonstrated exceptional performance. Sex-based analyses revealed that optimal cut-off values varied, with most indices maintaining a consistent discriminatory capacity across sexes.ConclusionsNon-conventional anthropometric indices, particularly those incorporating metabolic and anthropometric parameters, outperform traditional BMI-based assessments for CMR stratification in Mexican adults. These accessible, cost-effective tools offer superior diagnostic accuracy and enhance early identification of high-risk individuals in resource-limited healthcare settings. Future studies are required to validate these findings and establish population-specific reference values.